Gastroesophageal Reflux in Children - Kanber, Y.; Kalaycı, A.G. (My University, 2001)
Gastroesophageal reflux (GER) is a common problem in infants and young children, but the mechanical events that lead to its intermittent occurrence are poorly understood. GER is an occasional physiological event in normal adults and children, but becomes pathological when its intensity or frequency increases or when complications arise. Diagnostic recommendations include the following: (1) general approach to GER. including patient's symptoms, (2) appropriate mucosal evaluation and (3) use of pH and provocative testing. Therapeutic recommendations include the following: (1) general approach to therapy including lifestyle and nutritional changes, (2) use of acid suppression, (3) use of promotility drugs, (4) maintenance treatment of GER, and (5) indications for antireflux surgery.
Çocuklarda Gastroözofageal Reflü
Keywords: Childhood; Gastroesophageal Reflux